ТЕХНОЛОГИЧЕСКИЕ СПОСОБЫ ПОВЫШЕНИЯ ИЗНОСОСТОЙКОСТИ И ДОЛГОВЕЧНОСТИ ПРИ РЕСТАВРАЦИИ ДЕТАЛЕЙ - Ибрагимов, Джахангир Солижанович (Educational Research in Universal Sciences, 2023)
Improving the reliability and service life of machines, components, and units are an important factor in reducing the cost of restoration, downtime of equipment in repair, reducing the number of spare parts. The introduction of the latest technologies of agricultural production, as well as constant modern improvement, the complexity of machinery is a natural result of its development. A promising direction of restoration technology in the organizational plan is the deepening of the method of group restoration technology - the creation of unified group equipment for the restoration of surfaces. It is established that the majority of details of the restored cars are rejected at the expense of insignificant wear of working surfaces, making no more than 1% of initial weight of details. Experiments and practice show that the repair of agricultural machinery is technically impossible to avoid. Most worn parts have a high residual value: their restoration consumes 20-30 times less metal and materials than the manufacture of new ones, which is economically feasible.